Peran Fintech Syariah Dalam Mendorong Investasi Berbasis ESG (Environmental, Social, Governance) di Pasar Modal Syariah Digital - Putri, Fitriani Wijaya; Samsuri, Andriani (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
Islamic fintech is a financial technology innovation that integrates sharia principles with modern financial services, and now plays a strategic role in encouraging ESG (Environmental, Social, Governance) based investments. As global awareness of the importance of sustainable development increases, Islamic fintech is emerging as an inclusive solution that not only complies with Islamic values, but also supports socially and environmentally responsible economic growth. This study aims to analyse how Islamic fintech implements ESG values, by examining its mechanisms, technological innovations, as well as its impact on environmental, social, and governance. Using a qualitative approach through literature review and secondary data analysis, this study found that Islamic fintech has successfully encouraged sustainable investment through various initiatives, such as Islamic crowdfunding for green projects, sustainability oriented MSME financing, and Green Sukuk issuance. The use of blockchain technology contributes to increased transparency and accountability, while Islamic financial literacy programmes expand people's understanding of the importance of ESG minded investments. In addition, close collaboration with Islamic financial institutions and regulators ensures compliance with sharia principles and ESG standards. The results of this study confirm that Islamic fintech is not only a modern financial instrument, but also a change agent capable of expanding access to sustainable investments and strengthening an inclusive and ethical financial ecosystem.